GM1 Induced the inflammatory response related to the Raf-1/MEK1/2/ERK1/2 pathway in co-culture of pig mesenchymal stem cells with RAW264.7. Issue 3 (4th May 2018) - Kwak, Dong Hoon; Seo, You Na; Lee, Ju Hyoung; Park, Soon Ju; Cho, Young Ho; Kim, Ji-Su; Kim, Sun-Uk; Choo, Young-Kug
ABSTRACT: Pig-human xenotransplantation can trigger cell-mediated immune responses. We explored the role of gangliosides in inflammation related to immune rejection in xenotransplantation. Co-culture of xenogeneic cells (pig-MSCs and RAW264.7) was used to emulate xenotransplantation conditions. MTT assay results indicated that cell viability was significantly decreased in pADMSCs co-cultured with RAW264.7 cells. GM1 and GM3 were highly expressed in pADMSCs co-cultured with RAW264.7 cells. pADMSCs co-cultured with RAW264.7 cells strongly expressed pro-inflammatory proteins such as COX-2, iNOS, p50, p65, pIκBα, and TNF-α. GM1-knockdown pADMSCs co-cultured with RAW 264.7 cells did not show significantly altered cell viability, but pro-inflammatory proteins were markedly inhibited. Co-culture of pADMSCs with RAW264.7 cells induced significant phosphorylation (p) of JNK1/2 and pERK1/2. However, pERK1/2 and pJNK1/2 were decreased and MEK1/2 and Raf1 were suppressed in GM1-knockdown pADMSCs co-cultured with RAW264.7 cells. Thus, the Raf-1/MEK1/2/ERK1/2 and JNK1/2 pathways were significantly upregulated in response to increases of GM1 in co-cultured xenogeneic cells. However, the inflammatory response was suppressed in co-culture of GM1-knockdown pADMSCs with RAW264.7 cells via down-regulation of the Raf-1/MEK1/2/ERK1/2 and JNK1/2 pathways. Therefore, the ganglioside GM1 appears to play a major role in the inflammatory response in xenotransplantation via the Raf-1/MEK1/2/ERK1/2 and JNK1/2 pathways.